“Cannabis Farming In Malana: A Socio-Legal Study Of Culture, Environment, And Law With A Comparative Perspective From Canada” (International Journal of Environmental Sciences, 2025)
Cannabis cultivation in the remote Himalayan village of Malana has long been integral to local culture and economy, yet it conflicts with India’s national narcotics laws. This paper provides a socio-legal analysis of Malana’s cannabis tradition, examining cultural norms, environmental impacts, and legal frameworks. It integrates case studies and official reports to describe how Malana’s unique self-governance and historic practices clash with the Narcotic Drugs and Psychotropic Substances (NDPS) Act (1985). The study also compares India’s approach with Canada’s legalized model, highlighting regulatory differences and outcomes. We review literature on Himalayan cannabis heritage, environmental studies of high-altitude cultivation, and cannabis policy. Key findings include that Malana’s harsh terrain leaves few viable crops besides cannabis and that eradication efforts drive illicit plantations into fragile forests, causing erosion. The Canadian experience shows that strict regulation and legal markets can reduce illicit trade, though challenges remain. Finally, we identify gaps in research on socio-environmental trade-offs and propose policy recommendations for India, such as permitting controlled hemp cultivation with local safeguards and investing in alternative livelihoods.